A STUDY ON THE RELATIONSHIP BETWEEN EMOTIONAL INTELLIGENCE, ACADEMIC SELF-EFFICACY AND ACADEMIC BURNOUT OF COLLEGE STUDENTS IN SHANXI PROVINCE, CHINA - Zheng, Guoyuan; Sun, Wenhong; Zhang, Weiming (Journal of Buddhist Education and Research (JBER), 2024)
Academic burnout exists in students' learning and has been explored in depth by many researchers to mitigate this phenomenon. This study investigated the mechanisms of influence between variables and used a questionnaire to complete the data sampling. According to the study's results, it was found that emotional intelligence and academic self-efficacy negatively influenced the occurrence of academic burnout. In contrast, emotional intelligence positively contributed to academic self-efficacy. To this end, this study explores the relationship between the variables, which has important theoretical implications for mitigating the occurrence of academic burnout.